(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2023)
Early childhood education (ECED) is an important phase in the formation of children’s knowledge base and character. This research focuses on the use of colouring activities as a method to develop early childhood creativity. This research adopted a descriptive qualitative approach. Data was collected through observation, interviews and document analysis. The data analysis process includes data reduction, data presentation and conclusion drawing. The result of the study is that colouring activities significantly contribute to the development of children’s creativity. Children’s creativity is seen through the way they choose and combine colours and their ability to colour within predetermined boundaries. PAUD Merpati Koperti Ambon teachers implement colouring activities by giving children the freedom to explore with colours, thus encouraging creativity and freedom of expression. Keywords: Early childhood education, creativity, colouring activities, child development